GEOCHEMISTRY OF POST-OROGENIC MAFIC DIKE ROCKS FROM THE EASTERN QUEEN MAUD LAND, EAST ANTARCTICA - シライシ, カズユキ; カニサワ, サトシ; イシカワ, ケンイチ; SHIRAISHI, Kazuyuki; KANISAWA, Satoshi; ISHIKAWA, Kenichi (National Institute of Polar Research, 1988)
P(論文) Two types of mafic dike rocks intruded the late Proterozoic metamorphic terrains of eastern Queen Maud Land : thermally metamorphosed rocks and unmetamorphosed rocks. The former is metamorphosed by ca. 500Ma granite intrusions, whereas the latter is Jurassic in age. The metadike rocks are continental tholeiites, although the geochemical character is variable from place to place. In particular, the rocks from the S∅r Rondane Mountains are transitional between quartz tholeiite and alkaline basalt. By analogy with other areas, the suggested tectonic environment for intrusion is an initial continental rift system. Unmetamorphosed dike rocks are similar in composition to Jurassic tholeiitic dike rocks from western Queen Maud Land. A Jurassic basalt-dolerite suite may widely occur under the continental ice of eastern Queen Maud Land. departmental bulletin paper